Oral health status of malnourished primary beneficiaries of operation blessing in Payatas, Quezon - de Lara, Andrea S.; Dee, Mary Ann Dorothy O. (Department of Community Dentistry, University of the Philippines Manila, 2008)
This study intended to determine the oral health status of malnourished primary beneficiaries of Operation Blessing in Payatas, Quezon City (QC). Average dmft, HI, height and weight of the primary beneficiaries as well as OHI-S scores were determined through oral examination. Interview guides of the subjects and ocular observations of the subjects' environment were also done. Result of the study showed that the average dmft of the different age groups were varied. Of the given age groups, the average dmft scores were 4,7,9,12, 10 while average OHI-S values were .66,.44,1.16,.93,.74 respectively. Most of the subjects claimed to brush their teeth 2-3x daily with the use of toothbrushes and toothpastes. In addition, they visit dentists only when needed. Subjects belong to financially-challenged class of society. based on high dmft scores (4, 7,9,12,10) and OHI-S values (.66,.44, 1.16,.93,.74) of malnourished primary beneficiaries of Operation Blessing in Payatas, Q.C. their oral health status is poor.